The preparation of phytosteryl succinyl sucrose esters and improvement of their water solubility and emulsifying properties. (30th March 2022) - Xia, Xue; Ren, Mingxing; He, Wen-Sen; Jia, Chengsheng; Zhang, Xiaoming
Highlights: Phytosteryl succinyl sucrose esters were prepared for the first time. The yield of phytosteryl esters was achieved at 84.3% by optimization. Addition of sucrosyl group improved water solubility and emulsion stability. Emulsifying activity of phytosteryl esters was 2.5 times that of phytosterols. Abstract: Phytosterols have gained much attention due to their outstanding cholesterol-reducing effect, while the insolubility in water limits their application. The aim of this study was to synthesize a novel hydrophilic phytosteryl derivatives-phytosteryl succinyl sucrose esters (PSSEs) and investigated their water solubility and emulsifying properties. PSSEs were synthesized by esterifying phytosterol hemisuccinates with sucrose through a mild chemical reaction. PSSEs were characterized by fourier transform infrared spectroscopy, mass spectroscopy, and nuclear magnetic resonance spectroscopy. The yield of PSSEs exceeded 84% in N, N -dimethylformamide for 36 h of reaction under the selected conditions: 100 mmol/L phytosteryl hemisuccinates, 150 mmol/L sucrose, 110 mmol/L 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide hydrochlide, 10 mmol/L 4-dimethylaminopyridine and 10 mmol/L p -toluenesulfonic acid. The water insolubility of phytosterols was overcome and the water solubility of PSSEs achieved 2.13 mg/mL. The emulsifying activity of PSSEs was 2.5 times that of phytosterols, reaching 0.95 mg/mL. PSSEs with better water solubility and emulsification properties could facilitate the widespread use of phytosterols in foods.